The Circulatory Effects of Increased Hydrostatic Pressure Due to Immersion and Submersion - Weenink, Robert P.; Wingelaar, Thijs T. (Frontiers in Physiology, 2021)
Increased hydrostatic pressure as experienced during immersion and submersion has effects on the circulation. The main effect is counteracting of gravity by buoyancy, which results in reduced extravasation of fluid. Immersion in a cold liquid leads to peripheral vasoconstriction, which centralizes the circulation. Additionally, a pressure difference usually exists between the lungs and the rest of the body, promoting pulmonary edema. However, hydrostatic pressure does not exert an external compressing force that counteracts extravasation, since the increased pressure is transmitted equally throughout all tissues immersed at the same level. Moreover, the vertical gradient of hydrostatic pressure down an immersed body part does not act as a resistance to blood flow. The occurrence of cardiovascular collapse when an immersed person is rescued from the water is not explained by removal of hydrostatic squeeze, but by sudden reinstitution of the effect of gravity in a cold and vasoplegic subject.